Factors influencing buying behavior of fashion clothing brands in Johor and Wilayah Persekutuan - Ur Rehman, Fazal (2019)
This study has focused on the issues in buying behavior of consumers toward the fashion clothing brands, as in Malaysian society, the fashion clothing brands are facing very hard time. Many fashion clothing brands have ended up their business and closed their shops. Hence, this study has emphasized on determining the right information, issues, gap of knowledge by evaluating the influence of social advertising, individual factors and brand image on the buying behavior of consumers along with the mediating role of brand image towards the fashion clothing brands based on the theory of reasoned action and technology of acceptance model. The theory of reasoned action and TAM model were selected due to the suitability of theoretical consideration. This study has collected data through questionnaires based survey from the consumers of fashion clothing brands in the State Johor and the Wilayah Persekutuan in Malaysia. This study has selected a sample size of 129 respondents based on G-Power and applied convenience-sampling technique to collect data through mall intercepts approach. Initially, a pilot study was conducted to ensure the accuracy and reliability of questionnaire and then progressed towards main study. The collected data have analyzed using SPSS and structural equation modeling through smart partial least square. The findings have revealed a positive significant relationship of social advertising, individual factors, and brand image with the buying behavior of consumers toward the fashion clothing brands in the State Johor and Wilayah Persekutuan at Malaysia. The findings have also revealed a positive significant relationship of social advertising and individual factors with the brand image among consumers. In addition, the results have shown that brand image mediates the relationship between social advertising, individual factors and the buying behavior of consumers. The results of this study have interesting implications for marketing research. Firm can better understand the market trend and consumers buying behavior by developing two ways communication. Firm can also stabilize their consumers and build the brand image using social advertising, and can enhance their marketing intelligence by using these factors.